The Influence Of Product Quality, Marketing Strategy, Price, And Location On The Purchase Decision Of Batik Batam At Dekranasda Kota Batam - Anggraini, Dini; Wibowo, Edwin Agung; Almira, Felia (Tractare: Jurnal Ekonomi-Manajemen, 2025)
This study aims to determine and analyze the effect of product quality, marketing strategy, price, and location on purchasing decisions for Batam batik at Dekranasda Batam City. This type of research is quantitative with a population of 750 respondents of Batik Dekranasda consumers in Batam. The sampling technique in this study used probability sampling using the Slovin formula so that a sample of 90 respondents was obtained. The data was obtained by using interview instruments and questionnaire instruments which had been tested for validity and reliability. Data analysis using multiple regression and hypothesis testing using SPSS version 26 test tool. The results of this study concluded that product quality has a significant effect on purchasing decisions, marketing strategies partially have a significant effect on purchasing decisions, prices partially have a significant effect on purchasing decisions, and location partially has a significant influence on purchasing decisions and simultaneous testing shows that product quality, marketing strategy, price, and location together have a significant effect on purchasing decisions